Chinese Land‐Based Interventions in Senegal. Issue 2 (15th March 2013) - Buckley, Lila; Wolford, Wendy; Borras, Saturnino M.; Hall, Ruth; Scoones, Ian; White, Ben
ABSTRACT As Chinese land‐based interventions multiply across the African continent, this article focuses on a single Chinese–Senegalese government‐run agriculture demonstration centre to provide insight into the daily realities of Chinese–African interactions on African land. Ethnographic methodologies are employed to examine practices and discourses on agricultural governance among Chinese and Senegalese informants. Building on theories of agriculture as performance, I show how distinct repertoires for land management are negotiated and reshaped by different subjects in a kind of improvised dance, where individuals' improvisations lead to unanticipated project outcomes. What emerges is a picture of a Chinese agricultural management regime for African land that is simultaneously fraught with conflict, while also replete with collaboration benefiting some smallholder farmers. This actor‐oriented approach provides a critical empirical lens as well as a research framework for engaging more constructively with Chinese in large‐scale land acquisitions. I argue that 'land grabbing' must be seen not as a straightforward, linear process of state or corporate takeover of global land, but as a dynamic performance of negotiation among diverse state actors, corporate players and citizens — one that will reshape global development in unanticipated ways.